Información No Divulgada y Secretos Comerciales en Chile - Egaña Bertoglia, Juan Pablo (Pontificia Universidad Católica del Perú, 2024)
The author analyzes the Trade Secrets statute in Chile, describing the decisive role of the international treaties TRIPS and the FTA with the USA, and the difficulties and inconsistencies observed in the implementation of its rules on undisclosed information in the domestic legal system. It also refers to the way in which the courts of justice and specialized adjudicating bodies applied this statute in the settlement of disputes arising under the Industrial Property and Access to Public Information laws, generating a jurisprudence that, despite the inconveniences of this statute, managed to achieve uniformity in the protection of undisclosed information, whether it was test data or Trade Secrets. Finally, it includes a look at the most recent legal amendments that affected the institution of Trade Secret in the criminal and industrial property fields, explaining how it is expected that they will contribute to strengthen this institution, thanks to the reference to the definition of Trade Secret of the Industrial Property Law, which is formulated when typifying the crime of violation of this institution in the criminal law.

El autor analiza el estatuto de Secretos Comerciales en Chile, describiendo el decisivo rol de los tratados internacionales ADPIC y el TLC con EE.UU., y las dificultades e inconsistencias que se observaron en la implementación de sus normas de información no divulgada en el sistema jurídico interno. También se refiere a la manera como los tribunales de justicia y órganos dirimentes especializados fueron aplicando ese estatuto en la solución de controversias planteadas en el ámbito de las leyes de Propiedad Industrial y Acceso a la Información Pública, generando una jurisprudencia que, pese a los bemoles de dicho estatuto, logró uniformarse en la protección de la información no divulgada, sea que se tratase de datos de prueba o Secretos Comerciales. Finalmente, se incluye una mirada a las más recientes modificaciones legales que afectaron a la institución del secreto somercial en los ámbitos penal y de propiedad industrial, explicando cómo se espera que ellas contribuyan a fortalecer esta institución, gracias a la remisión a la definición de secreto comercial de la ley de Propiedad Industrial, que se formula al tipificar el delito de violación de esta institución en la norma penal.
Undisclosed information and Trade Secrets in Chile
Keywords: Trade secret; Undisclosed information; Data protection; Undisclosed character; Reasonable measures; Comercial value; Secreto comercial; Información no divulgada; Protección de datos de prueba; Carácter secreto; Medidas razonables; Valor comercial; https://purl.org/pe-repo/ocde/ford#5.05.00